Thermally stable Pt/Ti mesh catalyst for catalytic hydrogen combustion. (24th June 2020) - du Preez, S.P.; Jones, D.R.; Warwick, M.E.A.; Falch, A.; Sekoai, P.T.; Mota das Neves Quaresma, C.; Bessarabov, D.G.; Dunnill, C.W.
Abstract: In this study, platinum (Pt) supported on titanium (Ti) mesh catalysts for catalytic hydrogen combustion were prepared by depositing Pt as a thin-layer on metallic or calcined Ti mesh. The Pt thin-layer could be stabilized as uniformly distributed, near nano-sized particles on the surface of calcined Ti mesh by exposing the freshly sputtered Pt to hydrogen. Temperatures between 478 and 525 °C were reached during hydrogen combustion and could be maintained at a hydrogen flow rate of 0.4 normal liter (Nl)/min for several hrs. It was determined that Ti mesh calcination at ≥900 °C formed an oxide layer on the surface of Ti wires, which prevented significant Pt aggregation. X-ray photoelectron spectroscopy revealed that the surface of Ti mesh was fully converted to TiO2 at ≥900 °C. Raman spectroscopy showed that the majority of TiO2 was present in the rutile phase, with some minor contribution from anatase-TiO2 . The calcined Ti support was stable through all investigations and did not indicate any signs of degradation. Highlights: Pt/Ti mesh catalyst were successfully developed for catalytic hydrogen combustion. Pt aggregation was limited/prevented on the surface of calcinated Ti mesh support. Catalyst maintained combustion temperatures of up to 525 °C. Catalytic combustion reaction became spontaneous above 70 °C.